حماية الإنسان من التعذيب في زمن السلم (دراسة مقارنة في ضوء أحكام الشريعة الإسلامية والقانون الدولي) - Khalil Mehemed Majaie (Universiti Sains Islam Malaysia, 2024)
This study discussed the position of Islamic Sharia and international law for human rights against acts of torture. The Islamic Sharia is rich with evidences on prohibition of torture, which was indicated in the holy Quran and the speech of prophet Mohammed peace be upon him as well as the way of life of prophet Mohammed’s companions (Sahabah) and the views of religious scholars, and some modern Islamic papers that indicated a definitive and comprehensive prohibition of torture without exemption or justifications, in addition to that the international law for human rights has specified regulations to prevent torture in time of peace embodied in the agreements and relevant international documents against torture,which was formed based on legal principles to prohibit torture in the international law of human rights. The study concluded that the legal and legitimate bases for prohibition of torture is characterized by strength and firmness, and emphasized that the continuous spread of torture phenomenon is not due to lake of legitimate regulations or legal texts against torture, but the main reason is failing in commitment to these regulations and control over execution. Therefore this research has simplified the means in Islamic Sharia to fight torture such as the mandate (wilayah) of the ombudsman, Islamic public opinion, and religious faith, and showed that these means could prevent torture and commitment in prohibition any kind of torture. This study explained the importance of these means and showed its significance in order to get benefit of Sharia regulations and using them to fight torture or reduce it. The international law for human rights includes various international means to protect human from torture in the time of peace, where official and international means with a governmental nature worked under special protection systems such as the reporting system and complains of nations and individuals to help victims and punish the offenders and criminals. Many international non-government organizations have been founded and significantly contributed to limit the crimes of torture, but the role of these organizations was limited. Therefore, these mean should be developed and support its systems in order to control the widespread of torture globally.